2013
DOI: 10.1088/0004-637x/763/2/87
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Analyses of Spectral Indices of Nonthermal Emissions Derived From Hard X-Rays and Microwaves

Abstract: We studied electron spectral indices of nonthermal emissions seen in hard X-rays (HXRs) and in microwaves. We analyzed 12 flares observed by the Hard X-ray Telescope aboard Yohkoh, Nobeyama Radio Polarimeters (NoRP), and the Nobeyama Radioheliograph (NoRH), and compared the spectral indices derived from total fluxes of hard X-rays and microwaves. Except for four events, which have very soft HXR spectra suffering from the thermal component, these flares show a gap ∆δ between the electron spectral indices derive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…of 0.97/0.88 are detected between the Fe XXI 1354.09Å blue shifts and the microwave 17/34 GHz emissions, a correlation coefficient of 0.87 is observed between the Fe XXI 1354.09Å blue shifts and the HXR 25−50 keV emission, and a correlation coefficient of 0.88 is found between the Fe XXI 1354.09Å blue shifts and the SXR 1.0−8.0Å flux derivative. Such high correlation coefficients demonstrate that the electron beams which might be accelerated by magnetic reconnection (e.g., Kundu et al 1994;Brosius & Holman 2007;White et al 2003;Asai et al 2013) drive the explosive chromospheric evaporation during the flare precursor Brosius et al 2016;Li et al 2017a). Meanwhile, the microwave and HXR emissions observed by NoRH and RHESSI images exhibit a pronounced brightening source that is co-spatial with the ribbon-like transient during the flare precursor peak, which gives an additional evidence of electron-driven evaporation before the GOES flare onset (Veronig et al 2010;Zhang et al 2016b;Li et al 2017b).…”
Section: Resultsmentioning
confidence: 98%
“…of 0.97/0.88 are detected between the Fe XXI 1354.09Å blue shifts and the microwave 17/34 GHz emissions, a correlation coefficient of 0.87 is observed between the Fe XXI 1354.09Å blue shifts and the HXR 25−50 keV emission, and a correlation coefficient of 0.88 is found between the Fe XXI 1354.09Å blue shifts and the SXR 1.0−8.0Å flux derivative. Such high correlation coefficients demonstrate that the electron beams which might be accelerated by magnetic reconnection (e.g., Kundu et al 1994;Brosius & Holman 2007;White et al 2003;Asai et al 2013) drive the explosive chromospheric evaporation during the flare precursor Brosius et al 2016;Li et al 2017a). Meanwhile, the microwave and HXR emissions observed by NoRH and RHESSI images exhibit a pronounced brightening source that is co-spatial with the ribbon-like transient during the flare precursor peak, which gives an additional evidence of electron-driven evaporation before the GOES flare onset (Veronig et al 2010;Zhang et al 2016b;Li et al 2017b).…”
Section: Resultsmentioning
confidence: 98%
“…Combined analysis of HXRs and microwaves reveal that the electron energy distribution inferred from the microwave spectrum is harder than that from the HXR spectrum; this result suggests an intrinsic spectral hardening for the source electron spectrum around several hundred keV (e.g., Silva et al 2000;Asai et al 2013). On the other hand, in a recent study by Kawate et al (2012), these authors concluded that electrons responsible for HXRs and microwaves have a common energy distribution and that the hardening of microwave emission is due to a more efficient trapping of electrons with higher energies.…”
Section: Introductionmentioning
confidence: 94%
“…Moses et al (1989) showed that in some flares the associated energetic electrons detected in-situ presented spectral hardening at high energies. Asai et al (2013) found that the electron spectral index deduced from the microwave emission was harder than that from the HXRs of the same source (also by Silva et al 2007), and deduced that the source electrons may be intrinsically hard at high energies. These studies provide additional support to the above interpretation of the high-energy hardening of the associated energetic electrons.…”
Section: Introductionmentioning
confidence: 96%